Advances in Understanding and Treating Oral Malignant Melanoma: A Comprehensive Review - Priya Devi; Sharon John; Shalini Gupta (Recent Updates in Disease and Health Research Vol. 2, 2024)
Primary oral melanoma is an exceptionally uncommon and aggressive tumor that emerges from the mucosal epithelium of the oral cavity, particularly in the upper jaw (palate or alveolar gingivae). Malignant melanoma originating outside the skin is an exceedingly rare condition and is recognized as one of the most lethal neoplasms in humans. Oral malignant melanoma (OMM) constitutes approximately 1% of all melanomas and accounts for roughly 0.5% of all oral malignancies. OMM has been documented in individuals aged 20 to 80 years, with a higher incidence in males. Due to the typically painless nature of mucosal melanotic lesions in their early stages, delayed identification and subsequent treatment contribute to a poorer prognosis.